Workplace violence and its strong association with depression among Brazilian workers: insights from a national survey - Faisal-Cury, Alexandre; Matijasevich, Alicia; Rodrigues, Daniel Maurício de Oliveira; Tabb, Karen M.; Peres, Maria Fernanda (Frontiers in Psychiatry, 2025)
ObjectiveWe aimed to investigate the association between workplace violence and depression among Brazilian workers.MethodsWe used a cross-sectional study using data from the Brazilian National Survey (PNS, 2019), a population-based study. A sample of 52,475 workers (18–98 years old; N = 22,797 women and 29,678 men) answered a questionnaire covering sociodemographic data, workplace violence (psychological and physical or sexual) in the last 12 months, and the Patient Health Questionnaire-9. Logistic regression models were performed and adjusted for sociodemographic factors. All analyses were conducted using weighted and stratified data by gender.ResultsThe prevalence of depression in this group of workers was 15.8% for women and 5.7% for men. Workplace psychological violence was reported by 4.4% of women and 4.9% of men. For physical or sexual violence, the figures were 0.5% for women and 0.6% for men. All types of violence were significantly associated with depression for women (psychological: OR: 3.37, 95% CI 2.31–4.93 and physical/sexual: OR: 2.44, 95% CI 1.15–5.15) and for men (psychological: OR: 4.07, 95% CI 3.13–5.27 and physical/sexual: OR: 3.88, 95% CI 1.06–5.27). Both types of workplace violence interacted with gender without noticeable differences between men and women.ConclusionWorkplace violence is associated with depression in both sexes. Preventive and management strategies for workplace violence are recommended.